A Needle in a Haystack: Relationship between Procedural Justice and Turnover Intention of Bank Workers in Nigeria - Fasanmi, Samuel Sunday; Fasanmi, Modupe Motunrayo (NIU Journal of Humanities, 2022)
The recent global pandemic has caused a lot of unprecedented changes in work-life and organisational policies. The banking industry was one of the hardest hit, with several employees laid off and some branches closing. The survivors' work lives and well-being matter to the overall effectiveness of the banking industry and the growth of the Nigerian economy. The researchers examine how procedural justice and turnover intention are related among bank workers. A total of one hundred and sixty-two staff members of First City Monumental Bank constituted the sample size for the study. A battery of standardised questionnaires was used for the survey. The two generated hypotheses showed that procedural justice and demographic variables are significantly, independently, and jointly influenced turnover intention among bankers in  in Nigeria. It was also found that procedural justice had a positive significant relationship with turnover intention among bank workers in Nigerian bank. It was suggested that the fairer the workers perceived the downsizing process, the better their reasoning with their management in coasting along with the downsizing process. Such positive feelings would lower turnover intention and jerk up the profit matrix of the banks. Keywords: Bankers, Procedural Justice, Sex, Turnover Intention.